What Do We Have to Know about PD-L1 Expression in Prostate Cancer? A Systematic Literature Review. Part 2: Clinic–Pathologic Correlations - Andrea Palicelli (MDPI AG, 2021)
Many studies have investigated the potential prognostic and predictive role of PD-L1 in prostatic carcinoma (PC). We performed a systematic literature review (PRISMA guidelines) to critically evaluate human tissue-based studies (immunohistochemistry, molecular analysis, etc.), experimental research (cell lines, mouse models), and clinical trials. Despite some controversial results and study limitations, PD-L1 expression by tumor cells may be related to clinic–pathologic features of adverse outcome, including advanced tumor stage (high pT, presence of lymph node, and distant metastases), positivity of surgical margins, high Grade Group, and castration resistance. Different PD-L1 positivity rates may be observed in matched primary PCs and various metastatic sites of the same patients. Over-fixation, type/duration of decalcification, and PD-L1 antibody clone may influence the immunohistochemical analysis of PD-L1 on bone metastases. PD-L1 seemed expressed more frequently by castration-resistant PCs (49%) as compared to hormone-sensitive PCs (17%). Some series found that PD-L1 positivity was associated with decreased time to castration resistance. Treatment with ipilimumab, cyclophosphamide/GVAX/degarelix, or degarelix alone may increase PD-L1 expression. Correlation of PD-L1 positivity with overall survival and outcomes related to tumor recurrence were rarely investigated; the few analyzed series produced conflicting results and sometimes showed limitations. Further studies are required. The testing and scoring of PD-L1 should be standardized.